PENGEMBANGAN MEDIA POP UP BOOK UNTUK MENINGKATKAN KEMAMPUAN PRESENTASI PADA PEMBELAJARAN IPAS KELAS IV SDN PAGERJAYA - Juita, Risma; Agatha Kristi Pramudika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background to this research problem is the low presentation skills of students. Based on interviews with fourth grade teachers, it is known that many students feel less confident in communicating, especially when they have to speak in front of the class. Apart from that, the low ability to speak in public is also caused by the lack of learning media in class IV at SDN Pagerjaya, so that when learning takes place, students often enjoy themselves with their friends. This research uses research and development methods with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The sample for this research was class IV students at SDN Pagerjaya. Data collection techniques used include interviews, documentation, and rubrics. This research produces Pop Up Book media to improve presentation skills in grade IV science and science learning at SDN Pagerjaya. The research results show that, based on validity assessments from material experts and media experts, the Pop Up Book media developed has met the valid criteria in the very good category. Responses from class IV students and teachers also show that this media is very suitable for use. Based on the results of the t test, H1 is accepted, which means that Pop Up Book media influences the presentation skills of class IV students.